Engineering Escherichia coli for renewable production of the 5‐carbon polyamide building‐blocks 5‐aminovalerate and glutarate. (17th January 2013) - Adkins, Jake; Jordan, Justin; Nielsen, David R.
Abstract Through metabolic pathway engineering, novel microbial biocatalysts can be engineered to convert renewable resources into useful chemicals, including monomer building‐blocks for bioplastics production. Here we describe the systematic engineering of Escherichia coli to produce, as individual products, two 5‐carbon polyamide building blocks, namely 5‐aminovalerate (AMV) and glutarate. The modular pathways were derived using "parts" from the natural lysine degradation pathway of Pseudomonas putida KT2440. Endogenous over‐production of the required precursor, lysine, was first achieved through metabolic deregulation of its biosynthesis pathway by introducing feedback resistant mutants of aspartate kinase III and dihydrodipicolinate synthase. Further disruption of native lysine decarboxylase activity (by deleting cadA and ldcC) limited cadaverine by‐product formation, enabling lysine production to 2.25 g/L at a glucose yield of 138 mmol/mol (18% of theoretical). Co‐expression of lysine monooxygenase and 5‐aminovaleramide amidohydrolase (encoded by davBA) then resulted in the production of 0.86 g/L AMV in 48 h. Finally, the additional co‐expression of glutaric semialdehyde dehydrogenase and 5‐aminovalerate aminotransferase (encoded by davDT) led to the production of 0.82 g/L glutarate under the same conditions. At this output, yields on glucose were 71 and 68 mmol/mol for AMV and glutarate (9.5 and 9.1% of theoretical), respectively. These findings further expand the number and diversity of polyamide monomers that can be derived directly from renewable resources. Biotechnol. Bioeng. 2013; 110: 1726–1734. © 2013 Wiley Periodicals, Inc.